(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: With the gradual evolution, cricket is generally regarded as a symbol of representation and tradition, but it has undergone appropriate changes over the last 50 years to sustain its growth and popularity. It would not be wrong to say that in this fast-paced and highly competitive world of sports, cricket needs to adapt to survive and thrive. Objectives: The present study was completed with following two objectives, which included (a) to determine the levels of awareness of safety measures of cricket players and (b) to explore the relationship between safety measures and risk management of cricket players. Hypotheses: The following hypotheses were formulated for the study; (a) There will be no significant differences between the levels of awareness of safety measures of cricket players and (b) There will be no significant relationship between the levels of awareness of safety measures and risk management among cricket players. Methodology: Respondents of the study comprised of the volunteer university Cricket players. Data were collected using the Safety Awareness Scale (SAS). Results: Out of the total respondents, 32.5% reported a history of diverse type of injuries. All participants showed a good level of safety awareness with a mean value of 17.95 and risk management with a mean value of 17.32. A significant relationship was found between safety awareness and risk management of the Cricket players.